Big data-based reference centiles for body composition in Korean children and adolescents: a cross-sectional study - Dohyun Chun; Seo Jung Kim; Junghwan Suh; Jihun Kim (BMC, 2024)
Abstract Background The changes in body composition during puberty not only contribute to the differences in body composition between adult males and females but also have associations with growth problems and metabolic disorders, including obesity. Therefore, understanding the changes in body composition during the pubertal period and analyzing reference values based on race and gender are essential research resources. The objective of this study was to generate reference centiles for body composition on a monthly basis using an extensive dataset of body composition information from Korean children and adolescents. Methods A total of 88,069 measurements from 22,515 children (11,062 boys and 11,453 girls) aged 7-16 years using a bioelectrical impedance analysis were included in the study after performing a Z-score-based data management procedure. Height, weight, body fat mass (BFM), and fat-free mass (FFM) were measured and used to derive body fat percentage (BF%), body mass index (BMI), fat mass index (FMI), and fat-free mass index (FFMI). Sex- and age-specific centiles were estimated using generalized additive models for location, scale, and shape with the Box-Cox Cole and Green distribution (i.e., lambda-mu-sigma method). Results The sex- and age-related disparities in body composition were most pronounced when weight was partitioned into BFM and FFM. In boys, the FFM increased markedly during pubertal growth spurts, whereas BFM remained relatively stable. In girls, the BFM increased steadily, whereas the rate of FFM increased slowly. The BMI increased steadily with age in both sexes. However, when BMI was parsed into FMI and FFMI, it became clear that the FFMI increased substantially during pubertal growth in boys, whereas the FMI peaked around age 11 and then declined. Conversely, the FMI increased steadily in girls, albeit with a slowing rate in the increase of the FFMI beginning around age 12. Conclusions This study produced age- and sex-specific reference percentiles for body composition indices in Korean children and adolescents using extensive biometric data.